Inspirasi Alquran dan Kearifan Lokal Untuk Meningkatkan Profesionalitas Tenaga Kerja - Jamil Abdul Aziz (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This article describes how Alquran and local wisdom in the archipelago can be an inspiration and guidance to Indonesian workers who work abroad to improve the quality and professionalism, so that as to achieve a better standard of living. There are at least nine characteristic points implied by the Quran which also correspond to the values of work ethic taught by local wisdom in the archipelago, among them: Amanah & Resilient, Intelligent, Diligent & Adaptive, Talk Less, Not Greedy, Do Worship Regularly, Honest, Thorough, Independent, Responsible.